Second-hand smoke exposure effects on nasal epithelia proteome - Neves, Sofia (2017)
Environmental second-hand smoke exposure (SHS) results in a statistically significant increase in the risk of diseases such cardiovascular diseases and lung cancer. Cigarette smoke contains thousands of constituents, including several carcinogens and cytotoxic chemicals that orchestrate chronic inflammatory responses and destructive remodeling events1,2. In this work, our main objective is to uncover biomarkers of SHS exposure effects by investigating the proteome of nasal epithelia from health subjects occupationally long–term exposed to SHS.